2009
DOI: 10.1111/j.1834-7819.2009.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment modalities in burning mouth syndrome

Abstract: Background: Burning mouth syndrome (BMS) is characterized by a spontaneous burning pain in the oral mucosa without known organic cause or standardized treatment. The aims of this study were to assess and compare the efficacy of clonazepam and diazepam in relieving the symptoms associated with BMS and evaluate for which patients this treatment might be effective by correlating treatment efficacy with underlying psychological status. Methods: The medical records of BMS patients attending an oral medicine private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
0
28
0
3
Order By: Relevance
“…These results reinforce the promising hypothesis that the aetiopathogeny of the BMS intercedes in a peripheral neurological alteration. There are several studies analyzing the effects of different BMS treatments (10,11,13,17). However, currently, there is no completely effective treatment for BMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results reinforce the promising hypothesis that the aetiopathogeny of the BMS intercedes in a peripheral neurological alteration. There are several studies analyzing the effects of different BMS treatments (10,11,13,17). However, currently, there is no completely effective treatment for BMS.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies published in the literature, the true aetiopathogeny of this disease still remains unknown, which hinders the advancement of the investigation of a treatment that totally effective (10,11,13,16). Some authors treat these symp-toms with capsaicin (17), some others with acid alpha-lipoic (alone or associated to gabapentin) (18,19), with antidepressants or benzodiacepines, such as clonazepam (7,20-22).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also shown a greater percentage of patients taking clonazepam reporting either partial or complete relief of symptoms compared to diazepam [21]. Neurosurgical exploration of the lingual nerve for glossodynia of neuropathic origin may relieve some of the more distressing symptoms, especially if there is a nodule of scar tissue or neuroma formation at the site of damage to the lingual nerve.…”
Section: Trigeminal Neuralgia:-mentioning
confidence: 99%
“…Some studies have also shown a greater percentage of patients taking clonazepam reporting either partial or complete relief of symptoms compared to diazepam [21].…”
Section: Palliative Care Treatments Burning Mouth Syndromementioning
confidence: 99%